Magnetohydrodynamics (MHD) boundary layer flow and heat transfer over shrinking sheet with suction and stability analysis - Mohd Adnan, Nurul Shahirah; Md. Arifin, Norihan; Bachok @ Lati, Norfifah; Md Ali, Fadzilah (Academy of Sciences Malaysia, 2019)
This case study seeks to examine the fluid flow over shrinking sheet towards suction. This works also investigate the heat transfer in the present of magnetic parameter, heat generation and Lewis number. The basic governing partial differential equations are reduced to a set of ordinary differential equations by using appropriate similarity transformation. To obtain the numerical results, we used MATLAB software. We notice the dual similarity solutions are available in certain range of shrinking sheet parameter. Thus, this results make us continue further in perform the stability analysis by using bvp4c solver in MATLAB software. As excepted, our study proved that the solution is stable only the first one and the second solution is not.